FACTORS INFLUENCING THE HISTORY OF THE GROWTH AND DEVELOPMENT OF ISLAMIC LAW FROM THE ERA OF THE PROPHET TO THE ABBASID PERIOD - Ritonga, Raja; Asmaret, Desi; Julhadi; Kamal, Tamrin; Saifullah (El-Ahli : Jurnal Hukum Keluarga Islam, 2024)
This article examines the historical factors that have influenced the growth and development of Islamic law over time. Islamic law, as one of the rich and complex legal systems, is not only influenced by primary normative sources such as the Qur'an and Hadith, but also by the social, political, and cultural dynamics in various regions and historical periods. Through a historical-analytical approach, this research explores various crucial determinants in the evolution of Islamic law, including its interactions with other civilizations, the development of religious thought, as well as political and economic transformations. The findings of this study suggest that the development of Islamic law is not a static phenomenon, but rather an ongoing process that continues to evolve in accordance with its historical context. A deep understanding of these factors is essential for grasping the adaptive nature of Islamic law across different parts of the world, as well as its relevance in addressing contemporary legal challenges